Experimental investigation and analytical verification of buckling of functionally graded carbon nanotube-reinforced sandwich beams - Emrah Madenci; Yasin Onuralp Özkılıç; Alireza Bahrami; Ceyhun Aksoylu; Muhammad Rizal Muhammad Asyraf; Ibrahim Y. Hakeem; Alexey N. Beskopylny; Sergey A. Stel'makh; Evgenii M. Shcherban; Sabry Fayed (Heliyon, 2024)
Carbon nanotube (CNT) reinforcement can lead to a new way to enhance the properties of composites by transforming the reinforcement phases into nanoscale fillers. In this study, the buckling response of functionally graded CNT-reinforced composite (FG-CNTRC) sandwich beams was investigated experimentally and analytically. The top and bottom plates of the sandwich beams were composed of carbon fiber laminated composite layers and hard core. The hard core was made of a pultruded glass fiber-reinforced polymer (GFRP) profile. The layers of FG-CNTRC surfaces were reinforced with different proportions of CNT. The reference sample was made of only a pultruded GFRP profile. In the study, the reference sample and four samples with CNT were tested under compression. The largest buckling load difference between the reference sample and the sample with CNT was 37.7%. The difference between the analytical calculation results and experimental results was obtained with an approximation of 0.49%–4.92%. Finally, the buckling, debonding, interlaminar cracks, and fiber breakage were observed in the samples.